INNOVATIVE IDEAS OF TEACHING POP VOCAL IN THE CONTEXT OF DECISION PROBLEMS OF UKRAINIAN VOCAL PEDAGOGY - Kulaha, Tetiana (Mountain School of Ukrainian Carpaty, 2020)
The article is devoted to the issues of pedagogical interaction and methods of teaching pop vocal and it is an overview of modern foreign publications that are freely available on the Internet. The study conducted from the standpoint of cultural-conformity and based on vital-axiological, holistic-emergent, praxiological, synergetic and thesaurus approaches, which actualize the direction of the educational process to enhance the creative mastery of relevant competencies and expand the boundaries of personal experience. This article outlines the problems of contemporary pop vocal pedagogy, namely: the lack of a holistic systematic scientific and methodological knowledge; use mainly the results of research conducted as early as the twentieth century; insufficient attention to the experience of foreign vocal teachers and art historians; academic focus, non cultural-conformity of content and recommended repertoire in programs for specialized music schools and art schools. It presents contemporary opinions, suggestions and recommendations regarding the organization and content of the educational process with pop singers. This is the role of the teacher in the educational process; integration of various arts; innovative teaching methods and types of musical activity corresponding to the current tendenses of musical and, in particular, vocal culture; features of contemporary vocal techniques, specific vocal qualities and methods of mastering them through the traditional bel canto technique; competencies necessary for pop singers; criteria for evaluating the results of training of a pop vocalist; the appropriateness of introducing jazz into a modern curriculum; issues of pop&jazz interpretation and improvisation. The article provides a description of non-traditional approaches characteristic of informal education and emphasizes promising of introducing them into a specialized art education. It is noted that the results of this study can be used in the development of a model for the formation of a pop vocal-performing thesaurus of high school students of institutions of non-formal specialized music education.